The Relationship of Social Interaction in The Family with The Adjustment of Students at School - Tiya Putri; Neviyarni Neviyarni (Jurnal Neo Konseling, 2019)
This research is motivated by the still low ability of students to adjust to school. Social interaction in the family is a factor that involves itself. This study aims to: (1) describe the social interactions of students in the family, (2) describe the conversations of students, (3) look for a significant relationship between family social interactions using students themselves. This study uses a quantitative method of descriptive correlational research. The study population was in class X students of SMA 7 Padang who tested 330 students. The sampling technique used was simple random sampling, so that a sample of 192 students was obtained. The instrument used was a student social interaction questionnaire in the family and a questionnaire translated by students. Data were analyzed by descriptive statistics and Pearson product moment technique using the SPSS version 20.0 program. The results of the study describe: (1) the social interaction of students in the family is in the good category, with an average achievement of 60.42%, (2) the middle class students in the very high category with an average achievement of 68.23%, and (3 ) There is a significant relationship between students' social interactions in families with students of 0.153 depending on the high level with a significance level of 0.034. The size of the conversation is 0.153, which means that the social interaction of students in a family is good, so students choose high. Conversely, if the social interaction of students in the family is not good, the conversation about students tends to be low. Guidance and Counseling Teachers are expected to provide group guidance services and group counseling so students can communicate better.